2002
DOI: 10.1021/ic0112138
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Nonlinear Optical Properties of Complexes with MM Triple and Quadruple Bonds (M = Mo, W) at 1064 nm by Degenerate Four-Wave Mixing

Abstract: Measurements of the third-order nonlinear optical responses of solutions of the metal-metal multiply bonded complexes Mo(2)(OPr(i))(6), W(2)(OBu(t))(6), M(2)(NMe(2))(6), M(2)(O(2)CBu(t))(4), and M(2)Cl(4)(PMe(3))(4) (M = Mo, W), using picosecond degenerate four-wave mixing at 1064 nm, are reported. These complexes display only very small instantaneous electronic polarizations when excited with cross-polarized beams. When the excitation beams are similarly polarized, a significant third-order optical response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The Re[c] values of the dinuclear complex of 2a at the two wavelengths are considered to be off-resonant values for one-photon absorption as well as for TPA. The values are less than 10 À33 esu, which are consistent with the report by Pate et al for similar dinuclear complexes of Mo and W atoms measured by picosecond DFWM at 1064 nm [3]. On the other hand, the Re[c] values of the tetranuclear complex of 1a at 800 nm is À6.6 · 10 À33 esu.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Re[c] values of the dinuclear complex of 2a at the two wavelengths are considered to be off-resonant values for one-photon absorption as well as for TPA. The values are less than 10 À33 esu, which are consistent with the report by Pate et al for similar dinuclear complexes of Mo and W atoms measured by picosecond DFWM at 1064 nm [3]. On the other hand, the Re[c] values of the tetranuclear complex of 1a at 800 nm is À6.6 · 10 À33 esu.…”
Section: Discussionsupporting
confidence: 91%
“…x expðÀixtÞ þ c:c:; For Conversion of v (3) in Convention II from that in convention I, a factor of 3 is multiplied as v ð3Þ ðÀx; x; Àx; xÞ ¼ 3 v ð3Þ ðÀx; x; Àx; xÞ. The convention of second hyperpolarizability c is the same for both conventions as v (3) = Nf 4 c, where N is number density of molecule and f is local field factor defined as f = (n 2 + 2)/ 3.…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…We had hoped that the alignment of MM multiple bonds might lead to some interesting large third-order nonlinear optical responses but more extensive studies of the optical responses of MM quadruply bonded complexes indicated that this was improbable (11). Thus, mesophases of these MM quadruply bonded complexes, although fascinating in their own right, would seem to have no immediate commercial use.…”
Section: Mesogensmentioning
confidence: 99%
“…This limbo has subphases determined by the order induced by the type of molecules and their responsiveness to outside influences such as magnetic fields or temperature. Chisholm examines how the MM axes are aligned in magnetic fields, characterizes the properties with regard to temperature, and looks for third-order responses (9,10). He says it was disappointing not to find any large thirdorder responses because it means that the MM bonds cannot be used in laser applications.…”
Section: Liquid Crystal Limbomentioning
confidence: 99%